Novel variants associated with premature ovarian insufficiency in Russian adolescents - Tsabai, Polina; Kumykova, Zaira; Averkova, Victoria; Pavlova, Nadezhda; Maslennikov, Dmitry; Bolshakova, Anna; Batyrova, Zalina; Kolpakova, Tamara; Bystritskiy, Andrey; Karetnikova, Natalia; Ekimov, Alexey; Goltsov, Andrey; et al. (Frontiers in Endocrinology, 2025)
IntroductionWhile variants in hundreds of genes have been linked to premature ovarian insufficiency (POI), monogenic disorders account for fewer than half of idiopathic POI cases in adolescents with 46,XX karyotype. This highlights the need for the further genetic investigation across diverse populations.Patients and methodsWe recruited 63 Russian patients diagnosed with 46,XX POI before age 18. All underwent FMR1 premutation testing and whole-exome sequencing (WES). Copy number variation (CNV) analysis was conducted on WES data. Segregation studies by Sanger sequencing were performed where samples from the patients’ relatives were available.ResultsWe identified variants in 15 genes in 38% of the cohort, including 13 causative genes (FMR1, DCAF17, FOXL2, STAG3, TP63, BNC1, CPEB1, NOBOX, LMNA, FSHR, SPIDR, MCM8, EIF2B2) and 2 candidate genes (MYRF, LATS1). 3.2% of patients carried an FMR1 premutation. WES detected causative single nucleotide variants (SNVs) in 15 patients (17.5% of the cohort). CNV analysis increased the diagnostic yield to 20.6%, identifying 15q25.2 microdeletions (BNC1, CPEB1) in two patients and FSHR exon 2 deletion in one patient with resistant ovary syndrome. Overall, the combination of molecular genetic approaches established a diagnosis of monogenic POI (pathogenic or likely pathogenic variants) in 23.8% of adolescents with normal female karyotype. 5 patients (7.9%) carried variants of unknown significance in FSHR, LMNA, NOBOX, SPIDR, LATS1 genes, warranting further investigation.DiscussionOur findings demonstrate that WES is an effective diagnostic tool for adolescents with POI and should supplement standard karyotyping and FMR1 testing in routine clinical practice. We report several novel variants in POI-associated genes and propose new gene-disease association.